2021
DOI: 10.1039/d0ma00795a
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, evidence, and effect of junction clustering in supramolecular polymer materials

Abstract: In this review, the origin of clusters in supramolecular polymer materials, their characterization, their effects on the dynamic and mechanical properties, and their potentials for designing functional materials are overviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 203 publications
(385 reference statements)
0
57
0
Order By: Relevance
“…Such a clustering of the supramolecular stickers is generally known to enforce networks if it contributes to a higher coordination number, stabilizes weak supramolecular bonds, or develops intrachain connections to elastically active interchain junctions. 24 In view of these insights and the DLS measurements performed on the precursor polymer solutions, a likely explanation for the enhancement of the here-in investigated PU gels is therefore a comparable sticker aggregation. Based on the calculated mass fraction of the aggregates (≈10 wt %), we suspect the PU networks to be a mixture of binary sticker assemblies with randomly distributed clusters with higher functionalities.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Such a clustering of the supramolecular stickers is generally known to enforce networks if it contributes to a higher coordination number, stabilizes weak supramolecular bonds, or develops intrachain connections to elastically active interchain junctions. 24 In view of these insights and the DLS measurements performed on the precursor polymer solutions, a likely explanation for the enhancement of the here-in investigated PU gels is therefore a comparable sticker aggregation. Based on the calculated mass fraction of the aggregates (≈10 wt %), we suspect the PU networks to be a mixture of binary sticker assemblies with randomly distributed clusters with higher functionalities.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Here, cryo-transmission electron microscopy revealed that the Upy–Upy interactions are shielded from the aqueous surrounding in segregated pockets comprising Upy aggregates. Such a clustering of the supramolecular stickers is generally known to enforce networks if it contributes to a higher coordination number, stabilizes weak supramolecular bonds, or develops intrachain connections to elastically active interchain junctions . In view of these insights and the DLS measurements performed on the precursor polymer solutions, a likely explanation for the enhancement of the here-in investigated PU gels is therefore a comparable sticker aggregation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Here phase transformation between the perforated nanovesicle and nanovesicle was achieved through changes in the system temperature. Supramolecular nanoaggregates that are driven by hydrogen bonding interactions have also attracted much attention 40–44 . The hydrogen bonding force is influenced by temperature, pH and solvent polarity; therefore, stimuli‐responsive supramolecular nanostructures can be prepared by employing molecules with hydrogen bonds, with potential applications in various materials, such as memory and self‐healing materials 45–49 …”
Section: Introductionmentioning
confidence: 99%